KAJIAN PERMINTAAN STANDAR NASIONAL INDONESIA (SNI) MELALUI PNPB DI PERPUSTAKAN BSN - Abdul Rahman Saleh; Erni Sumarni; Muhammad Baharudin; Nursidik Fadilah (Perpustakaan Nasional RI, 2016)
Indonesia National Standard (SNI) is a list of standards approved by the National Standard Board (BSN). SNI are distributed by BSN through certain ways such as the BSN official website. SNI can also be distributed to Technical Committee secretariats in ministries/institutions to be used relevantly by stakeholders. The other way of distribution is through Non-Tax National Income (PNPB) procedure. By using this procedure, applicants have topay for a certain amount of fee in turn for reproduction process. This study is aimed at observing demands of SNI. From stakeholders made through PNBP procedure during 2012 to 2015. The result shows that there are considerably high number of demands for old SNI made by stakeholders.